Study of the somaclonal variation produced by different methods of polyploidization in Asparagus officinalis L. - Regalado González, Jose Javier (2015)
Polyploid plants have been induced in different Asparagus officinalis L. breeding programs in order to obtain plants with improved agronomical traits, such as large spear diameter or segregation ratios with a higher number of males. The polyploidization methods can produce somaclonal variation in the polyploid plants obtained and, therefore, unwanted changes in the agronomical traits of the initial elite plants. We used two different polyploidization methods to induce polyploid plants from diploid genotypes of commercial varieties and tetraploid genotypes of the Spanish landrace “Morado de Huétor”. The first method was the culture of rhizome buds in the medium ARBM-3 (Asparagus Rhizome Bud Medium), supplemented with different concentrations of colchicine (0.1–0.75 g l−1) for 10 and 20 days. The best polyploidization rate obtained was 25 % (0.5 g l−1 colchicine for 10 days). The second method was the regeneration of polyploid plants from callus culture, resulting in a polyploidization rate of 40 and 12.5 % for the diploid genotype CM077 and the tetraploid genotype HT156, respectively. Additionally, we have developed a new protocol to separate the mixoploids generated into their different genetic components, obtaining plants with a unique ploidy level. EST-SSRs markers were employed to analyze the genetic stability of polyploidy plants. Somaclonal variation was not detected for polyploidy plants obtained through the culture of rhizome bud explants. Therefore, these polyploid plants should maintain the agronomical traits of the initial elite plants. However, somaclonal variation was detected in the polyploid plants regenerated from callus culture.